2020
DOI: 10.1371/journal.pone.0224956
|View full text |Cite
|
Sign up to set email alerts
|

Social and endogenous infant vocalizations

Abstract: Research on infant vocal development has provided notable insights into vocal interaction with caregivers, elucidating growth in foundations for language through parental elicitation and reaction to vocalizations. A role for infant vocalizations produced endogenously, potentially providing raw material for interaction and a basis for growth in the vocal capacity itself, has received less attention. We report that in laboratory recordings of infants and their parents, the bulk of infant speech-like vocalization… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 70 publications
(89 reference statements)
1
59
1
Order By: Relevance
“…Infants produce more speech-like vocalizations, or "protophones," (including both canonical and precanonical babbling) without person-directed gaze (both when alone and in the presence of caregivers) than they produce socially-directed sounds (Harold & Barlow, 2013;Oller et al, 2013). More recently, several authors of the present study found that approximately 75% of all infant protophones in laboratory recordings were endogenously produced (Long et al, 2020). We know that social interaction influences infant babbling, phonological learning, and complex language skills (Albert et al, 2018;Elmlinger et al, 2019;Goldstein et al, 2003;Goldstein & Schwade, 2008;Kuhl, 2007), but social and endogenous motivations for infant vocal activity require additional research to elucidate their relative roles.…”
Section: The Social and Endogenous Nature Of Infant Vocalizationsmentioning
confidence: 45%
See 4 more Smart Citations
“…Infants produce more speech-like vocalizations, or "protophones," (including both canonical and precanonical babbling) without person-directed gaze (both when alone and in the presence of caregivers) than they produce socially-directed sounds (Harold & Barlow, 2013;Oller et al, 2013). More recently, several authors of the present study found that approximately 75% of all infant protophones in laboratory recordings were endogenously produced (Long et al, 2020). We know that social interaction influences infant babbling, phonological learning, and complex language skills (Albert et al, 2018;Elmlinger et al, 2019;Goldstein et al, 2003;Goldstein & Schwade, 2008;Kuhl, 2007), but social and endogenous motivations for infant vocal activity require additional research to elucidate their relative roles.…”
Section: The Social and Endogenous Nature Of Infant Vocalizationsmentioning
confidence: 45%
“…We and others have hypothesized selection pressures on the production of endogenously produced protophones. Baby sounds can be seen as fitness signals selected to elicit longterm investment from caregivers, required across the lengthy period of relative helplessness, or altriciality, of infant humans (Locke, 2017;Long et al, 2020;Oller et al, 2016Oller et al, , 2019. In accord with the fitness signaling hypothesis, the quality of infant vocalizations can be considered a salient and reliable signal of fitness.…”
Section: An Evolutionary-developmental Perspective On the Role Of Socmentioning
confidence: 99%
See 3 more Smart Citations